Al-‘Alāqah bayna Mabādi’ ‘Ilm Al-Tasawwuf wa ‘Ilm Al-Fiqh inda Imam al-Ghazali - Rif'at Husnul Ma'afi; Aidil Putra Syurbakti; Maria Ulfa (Universitas Darussalam Gontor, 2022)
One of the major contributions of Imam al-Ghazali through his book Ihya' Ulumuddin is the discussion of the close relationship between Sufism and fiqh. It is said so, because there are differences in understanding and conflict between groups who tend to pay too much attention to fiqh and ignore tasawuf and even deny it. Some other groups are immersed in the flow of Sufism so that they seem to ignore the Shari'a with the excuse that they are close to Allah SWT. Through Ihya, al-Ghazali explained that Sufism and Jurisprudence cannot be separated from each other, but must be practiced simultaneously. The goal is to reach an inner feeling that is touched by the wisdom in the worship. Like prayer, if the conditions are met, a Muslim should present a humble heart by understanding every meaning of dhikr in it. Likewise zakat, if the physical requirements have been fulfilled, a Muslim should hasten zakat with the intention to cleanse the heart of miserliness and avoid being riya'. In fasting, basically it is not enough just to refrain from eating and drinking, but the essence of fasting is to refrain from doing anything that is hated by Allah SWT and also to refrain from lust and worldly desires.